Halal Science Authentication and Functional Characterization of Local Lampung Tuber Polysaccharides as Emulsifier Substitution in the Food Industry - Welly Anggraini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
As the 2026 deadline for mandatory halal certification in Indonesia approaches, concerns regarding the halal status of imported emulsifiers, particularly E471 (mono- and diglycerides of fatty acids), remain a significant issue. The primary problem lies in halal critical points that are extremely difficult to trace: these materials may be derived from hydrolysed animal fats (bovine or porcine), not slaughtered according to Islamic law. This research aims to explore the functional properties of polysaccharides from local Lampung tubers, namely Porang and Gembili, as authenticated halal emulsifier substitutes. The study employed a Factorial Completely Randomized Design (CRD), testing tuber sources and concentration levels of 1%, 3%, and 5%. Polysaccharides were extracted via freeze-drying and subsequently characterized using physicochemical analysis and FTIR spectroscopy. Based on the results, 3% Porang polysaccharide produced a low Creaming Index (CI) of 3.1 ± 0.3% after 14 days and a high viscosity of 45,200 cP. Statistically, this stability did not differ significantly (p > 0.05) from the commercial E471 standard in its capacity to form an effective interfacial layer that prevents coalescence. The material was authenticated by the absence of a carbonyl absorption peak at 1745 cm⁻¹ in its FTIR spectrum, as part of a molecular halal authentication assessment. This provides scientific proof that the isolates are not contaminated by animal fats or questionable substances. This study concludes that Porang glucomannan and Gembili mucilage are strategic